Analysis of Psychological Well-Being among Migrant Communities - Safarina, Nur Afni; Amin, Safuwan; Dewi, Rahmia; Amalia, Ika (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2023)
This qualitative study aims to analysis the reality of psychological well-being (PWB) within immigrant communities in around Unimal Campus, Reuleut, Aceh. The primary objectives are to establish a model of psychological well-being specific to migrant communities in this locality and to identify the key factors that exert influence on their psychological well-being. The factors under investigation include economic status, social support, social networks, religiosity, personality traits, emotional regulation, and loneliness. By adopting a phenomenology qualitative approach, this research seeks to provide a comprehensive understanding of the experiences of immigrant communities in Reuleut. The study's subjects comprise immigrant communities residing in Reuleut, Aceh. Through in-depth interviews and thematic analysis, the research sheds light on the nuanced dimensions of psychological well-being within this context. The findings contribute to the broader understanding of psychological well-being factors that resonate within migrant communities, thereby presenting an informed perspective on the conditions and challenges faced by immigrants in Aceh. The outcomes of this study reveal that gender does not significantly impact the manifestation of resistance behaviors among students. The study underscores that both male and female students exhibit moderate levels of resistance towards teachers. This lack of gender-related distinctions in resistance levels underscores the potential influence of other factors, such as pedagogical approaches, classroom dynamics, and student perceptions. Consequently, this research underscores the imperative of cultivating positive teacher-student interactions and fostering an environment where students' voices are valued and comprehended, irrespective of their gender.